Prepotent Response Inhibition and Interference Control in Autism Spectrum Disorders: Two Meta‐Analyses. Issue 4 (4th March 2014) - Geurts, Hilde M.; van den Bergh, Sanne F. W. M.; Ruzzano, Laura
<x xml:space="preserve">Abstract</x> There is a substantial amount of data providing evidence for, but also against the hypothesis that individuals with autism spectrum disorders (ASD) encounter inhibitory control deficits. ASD is often associated with interference control deficits rather than prepotent response inhibition. Moreover, the developmental trajectory for these inhibitory control processes is hypothesized to differ in ASD as compared to typical development. In efforts to gain a more comprehensive perspective of inhibition in ASD, separate quantitative analysis for prepotent response inhibition studies and interference control studies were conducted. Together, these two meta‐analyses included 41 studies with a combined sample size of 1, 091 people with ASD (M age 14.8 years), and 1, 306 typically developing (TD) controls (M age 13.8 years).The meta‐analyses indicated that individuals with ASD show increased difficulties in prepotent response inhibition (effect size 0.55) and in interference control (effect size 0.31). In addition, age was a relevant moderator for prepotent response inhibition but not for interference control. Exploratory analyses revealed that when IQ was taken into account, heterogeneity considerably decreased among interference control studies but not among prepotent response inhibition. In contrast to the general belief, both prepotent response inhibition and interference control problems were observed in individuals with ASD. However, a large variation between studies was also found. Therefore, there remain factors beyond inhibition type, age, or IQ that significantly influence inhibitory control performance among individuals with ASD. Autism Res2014, 7: 407–420. © 2014 International Society for Autism Research, Wiley Periodicals, Inc.